Polo-like kinase-1 controls Aurora A destruction by activating APC/C-Cdh1. - Renske van Leuken; Linda Clijsters; Wouter van Zon; Dan Lim; XueBiao Yao; Rob M F Wolthuis; Michael B Yaffe; René H Medema; Marcel A T M van Vugt (PLoS ONE, 2009)
Polo-like kinase-1 (Plk1) is activated before mitosis by Aurora A and its cofactor Bora. In mitosis, Bora is degraded in a manner dependent on Plk1 kinase activity and the E3 ubiquitin ligase SCF-betaTrCP. Here, we show that Plk1 is also required for the timely destruction of its activator Aurora A in late anaphase. It has been shown that Aurora A destruction is controlled by the auxiliary subunit Cdh1 of the Anaphase-Promoting Complex/Cyclosome (APC/C). Remarkably, we found that Plk1-depletion prevented the efficient dephosphorylation of Cdh1 during mitotic exit. Plk1 mediated its effect on Cdh1, at least in part, through direct phosphorylation of the human phosphatase Cdc14A, controlling the phosphorylation state of Cdh1. We conclude that Plk1 facilitates efficient Aurora A degradation through APC/C-Cdh1 activation after mitosis, with a potential role for hCdc14A.